2013
DOI: 10.1177/0956462413477552
|View full text |Cite
|
Sign up to set email alerts
|

Increasing screening frequency in men who have sex with men: impact of guidance on risk profiling on workload and earlier diagnosis of sexually transmitted infection and HIV

Abstract: Increasing screening frequency in men who have sex with men (MSM) engaging in high-risk behaviours can reduce prevalence of sexually transmitted infections (STIs). This evaluation investigated the impact of applying stricter screening guidelines for MSM on service workload and earlier STI diagnoses. A validated risk assessment tool (RAT) was distributed to MSM attending a level 3 sexual health service over three months. Australian screening guidelines were applied to the data to identify MSM requiring more fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
9
0
3
Order By: Relevance
“…The majority of the evidence came from 20 modelling studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). There was one descriptive study (38); three non-economic modelling studies (39)(40)(41); one cohort study (42); one cross-sectional study (43); and one mixed-methods study (descriptive and modelling) (44). The included studies were conducted in various countries, including 14 in the United States (US), three in Australia and two in the United Kingdom (UK).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the evidence came from 20 modelling studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). There was one descriptive study (38); three non-economic modelling studies (39)(40)(41); one cohort study (42); one cross-sectional study (43); and one mixed-methods study (descriptive and modelling) (44). The included studies were conducted in various countries, including 14 in the United States (US), three in Australia and two in the United Kingdom (UK).…”
Section: Resultsmentioning
confidence: 99%
“…The search identified 14 studies that addressed the optimal HIV screening interval among MSM. Eight studies were economic modelling studies (19,20,(22)(23)(24)(25)32,37) and five were modelling studies without economic inputs (38,(40)(41)(42)44). Recommended testing frequencies ranged from one-time only, to annually and to once every three months.…”
Section: Men Who Have Sex With Menmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a lack of consistent evidence about what constitutes ‘high risk’ 7. One study found defining high risk as unprotected anal intercourse, 10 or more partners in the last 6 months, chemsex or group sex showed the greatest potential gains 24. Our questions aim to identify high-risk sexual behaviours and those who require hepatitis C testing, and those who have not visited our service before, to ensure that all MSM are being seen in person at some point.…”
Section: Discussionmentioning
confidence: 99%
“…EXAMEN SYSTÉMATIQUEétude descriptive(38), trois études de modélisation non économique(39)(40)(41), une étude de cohorte(42), une étude transversale(43) et une étude combinée (descriptive et de modélisation)(44). Les études comprises ont été menées dans divers pays, y compris 14 aux États-Unis, trois en Australie et deux au RoyaumeUni.…”
unclassified